Auxin biosynthesis site and polar transport in maize coleoptiles - Nishimura, Takeshi (Plant Signal Behav, 2010)
Since Darwins’ pioneering experiments, monocot coleoptiles have been used to investigate indole-3-acetic acid (IAA) production and polar transport. In a recent study, using maize coleoptiles, we first showed that the asymmetric IAA flow from the tip in response to gravistimulus directly affects the TIR/AFBs-mediated auxin signaling pathway, which results in tropic curvature. In this work, we also showed that IAA is synthesized from tryptophan (Trp) in the apical 1 mm region, and from there the synthesized IAA moves to the basal part via polar transport by ZmPIN1(s). These results clearly show the importance of the tip region in perception of gravistimulus and in transmitting the perceived information to the lower region using IAA as a messenger signal. Thus, it is concluded that IAA production and transport from the tip are key factors controlling the cell elongation rate in the lower part of the coleoptiles, by making a regulated and dynamic IAA flow net work in the coleoptiles.